PCP Removal by Sulfate Radical and Microwave (SR/MW) from Aqueous Solutions (Global Journal of Science Frontier Research, 2014)
Pentachlorophenol (PCP) is one of the most pollutants frequently used in fungicides and pesticides. Its toxicity is due to intervention with oxidative phosphorylation. Acute and chronic PCP poisoning are approved in human and other living organisms. Recently, AOPs based on microwave and sulfate radical (SO 4 0-) have created many great scientific interests due to its high efficiency in the degradation and mineralization of recalcitrant and/or toxic organic pollutants. So that in this study for removal of PCP from wastewater, microwave/persulfate(MW/SPS) was used. The effects of operational parameters such as pH of solution, the power of microwave radiations and the amount of persulfate concentration were studied. Spectrophotometer and HPLC instruments were used for determining the concentration of PCP. The experimental results showed that the removal of PCP was influenced by many factors, such as the pH value, the amount of persulfate and microwave power. The optimum conditions for the best removal rate were obtained at pH=11, a persulfate concentration of 0.02mol/L and microwave irradiation power of 600W for MW/SPS system at constant PCP concentration. Also, obtained results showed that the removal of PCP by MW/SPS and MW alone were follow first order rate decay kinetics and the rate constants were 0.093 and 0.00066 min -1 , respectively.
Keywords: pentachlorophenol; oxidation process; microwave; persulfate